Intercropping sweet corn with two types of napier grass and legumes to enhance yield and nutritive quality of forage mixtures - Mohamad, Hafizan (2017)
Diversification cropping systems by multiple crop species, already considered as a way to solve some problems of modern agriculture which provides agronomic and economic options. The present study was conducted to determine the yield and nutritive quality of forage mixtures through intercropping sweet corn with Napier grasses and legumes. The specific objectives of this study were to determine the yield and to measure and compare the nutritive quality of forage mixtures of the sweet corn, Napier grasses, and legumes that cultivate through intercropping system. The study was conducted at Field 15, Crop Research Area and Nutritional Laboratory, Department Animal Science, Faculty of Agriculture, Universiti Putra Malaysia (UPM). The field study was carried out from June 2016 until August 2016. The experimental material consists of Sweet corn, tall Napier grass, dwarf Napier grass, and legumes with overall cultivation areas that was utilised about 15 m x 23 m. The treatments consist of four treatments with three replications including treatment 1 that intercrops between sweet corn with tall Napier grass (CTN). The treatment 2 was intercrops between sweet corn with tall Napier grass and legumes (CTL). The treatment 3 was intercrops between sweet corn with dwarf Napier grass (CDN). The treatment 4 was intercrops between sweet corn with dwarf Napier grass and legumes (CDL). The parameter of this study consists of vegetative production, chemical analysis, and botanical composition. In term of vegetative production, sweet corn plants height shows no significant difference (p<0.05) between all treatment but Napier grass plant height shows significantly difference (p<0.05) between treatments. Napier grass tiller number shows significantly difference (p<0.05) from week 1 until week 10 for all treatments. There are no significantly difference (p<0.05) between all treatments for sweet corn and legumes dry matter (DM) yield but Napier grass DM yield shows significantly difference (p<0.05) between all treatments. Leaf stem ratio (LSR) of sweet corn and Napier grass shows no significantly difference (p<0.05) between all treatments. In term of nutritive quality, the contents of dry matter (DM), ash, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) of sweet corn shows no significant difference (p<0.05) between all treatments. The contents of DM, CP and ADF for Napier grass shows significantly difference (p<0.05) between all treatments but shows no significant difference (p<0.05) between all treatments for contents of ash, NDF, and ADL. The contents of CP and NDF for legumes shows significantly difference (p<0.05) between all treatments but shows no significant difference (p<0.05) between all treatments for contents of DM, ash, ADF, and ADL. In conclusion, the study indicates that intercropping sweet corn with Napier grass and legume can increased dry matter (DM) yield and nutritive value of forage mixtures. In addition, the vegetative production of sweet corn did not affect the Napier grass but produces good nutritive quality to ruminants. However, the inclusion of legumes influenced the assessed vegetative production, nutritive quality, and botanical composition of intercrop plants that shows highest value when inclusion of legumes compared to the exclusion of legumes.